Localized Wnt-signaling promotes asymmetric NuMA-dependent oriented divisions and unequal apportioning of mitochondria - Eli, Susanna; Rauso, Greta; Ghezzi, Paola; Szczerkowski, James L. A.; Bruzzi, Michela; Rizzelli, Francesca; Iommazzo, Fabiola; Loffreda, Alessia; Castagna, Francesco; Donà, Federico; Gaddoni, Chiara; Dondi, Ambra; et al. (Nature communications, 2025)
In multicellular organisms, the execution of developmental and homeostatic programs often relies on asymmetric cell divisions. These divisions require the alignment of the mitotic spindle axis to cortical polarity cues, and the unequal partitioning of cellular components between progeny cells. Asymmetric divisions are orchestrated by signals from the niche frequently presented in a directional manner, such as Wnt signals. Here we employ bioengineered Wnt-niches to demonstrate that in metaphase NuMA/dynein microtubule motors form a complex with activated LRP6 and β-catenin at the cortical sites of Wnt activation to orient cell division perpendicularly. We show that engagement of LRP6 co-receptors by Wnt ligands locally stabilizes actomyosin contractility through the accumulation of myosin1C. Additionally, we describe a proteomic-based approach to identify mitotic protein complexes enriched at the Wnt-contact site, revealing that mitochondria polarize toward localized Wnt3a sources and are asymmetrically apportioned to the Wnt-proximal daughter cell during Wnt-mediated asymmetric cell division of embryonic stem cells. Mechanistically, we show that CENP-F is required for mitochondria polarization towards localized sites of Wnt3a activation, and that deletion of the Wnt-co-receptor LRP6 impairs the asymmetric apportioning of mitochondria. Our findings enhance the understanding of mitotic Wnt-signaling and elucidate fundamental principles underlying Wnt-dependent mitochondrial polarization. Asymmetric cell division often requires alignment of the mitotic spindle to cortical polarity cues. Here the authors show that cortical Wnt signaling induces formation of a complex between NuMA/dynein microtubule motors, LRP6 and β-catenin that promotes asymmetric division.